Increased serum B‐cell maturation antigen levels evaluated with an Elecsys‐based serum B‐cell maturation antigen assay have a negative prognostic value in patients with newly diagnosed multiple myeloma - Evangelos Terpos; Ioannis Ntanasis‐Stathopoulos; Panagiotis Malandrakis; Despina Fotiou; Magdalini Migkou; Evangelos Eleutherakis‐Papaiakovou; Foteini Theodorakakou; Maria Roussou; Maria Gavriatopoulou; Meletios A Dimopoulos; Efstathios Kastritis (eJHaem)
Abstract Background: Serum B‐cell maturation antigen (sBCMA) levels have emerged as a potential biomarker for disease monitoring in multiple myeloma (MM) with prognostic value. Methods: Herein, we evaluated the sBCMA levels in 166 patients with newly diagnosed MM with an Elecsys‐based sBCMA assay. Results: Increased sBCMA levels at diagnosis were correlated with inferior survival outcomes in terms of both progression‐free and overall survival. In a subset of patients with available samples at the time of disease progression, there was a trend for decreasing sBCMA values. Conclusion: Sequential evaluation of sBCMA in prospective studies will determine the value of incorporating sBCMA measurement in clinical practice.